THE ROLE OF HUMAN RESOURCE MANAGEMENT IN IMPROVING THE PERFORMANCE OF TECHNOLOGY-BASED ORGANIZATIONS - Khoirul Anam (PT. Arsil Reka Engineering, 2024)
In the dynamic technology business landscape, the key levers of success are human resources. This research examines the critical role of human resource management (HRM) in improving the performance of technology-based organizations. Through literature exploration and case studies, this research identifies six key HRM functions that contribute to performance: (1) strategic recruitment and selection to attract and retain skilled technology talent, (2) continuous development and learning to equip employees with relevant technology skills, (3) creation of innovative and collaborative work culture, (4) effective performance management systems to drive accountability and goal achievement, (5) competitive compensation and incentive strategies to motivate and retain employees, and (6) health and wellness programs that prioritize work-life balance and employee satisfaction. This research highlights the importance of technology integration in HRM, such as the use of digital recruitment platforms, online learning systems, and data analysis tools for data-driven decision-making. The findings show that proactive and adaptive HRM, which focuses on talent development, creation of a supportive work environment, and strategic use of technology, significantly improves the performance of technology-based organizations. This research offers practical insights for HRM practitioners and leaders of technology organizations to harness the potential of human resources and achieve competitive advantage in the digital age.